Biologics for allergy: therapeutic potential for ocular allergic diseases and adverse effects on the eye - Ken Fukuda; Tatsuma Kishimoto; Tamaki Sumi; Kenji Yamashiro; Nobuyuki Ebihara (Allergology International, 2023)
Biologics applying antibodies against IgE, IL-5, IL-5 receptor α, IL-4 receptor α, and IL-13 have dramatically improved recent treatment outcomes in allergic diseases including asthma, rhinitis, and atopic dermatitis. However, these drugs have not been approved for ocular allergic diseases such as allergic conjunctivitis, vernal keratoconjunctivitis, and atopic keratoconjunctivitis. Although the putative mechanisms suggest that these drugs should have beneficial effects in patients with ocular allergies and some studies have reported such beneficial effects, various adverse ocular symptoms have also been observed in clinical trials and off-label use studies. Since ocular allergic diseases have distinct pathogeneses, each biologic drug must be examined regarding specific effects on each ocular allergy. For example, IgE-mediated type 1 hypersensitivity plays a critical role in allergic conjunctivitis. By contrast, T cells and eosinophilic and non-IgE-mediated type 2 inflammation play important roles in vernal keratoconjunctivitis. Allergists must fully understand the effects of each drug on the eye. This review outlines both potential therapeutic and adverse effects of various biologics on allergic diseases of the eye.